PENGARUH DAYA TARIK PROMOSI CASHBACK DAN KEMUDAHAN TRANSAKSI TERHADAP KEPUTUSAN MENGGUNAKAN DOMPET DIGITAL SHOPEEPAY SEBAGAI DIGITAL PAYMENT - Rokhilawati, Yeni (Jurnal Istiqro, 2025)
The rapid progress of science and technology has had a huge impact on the payment system. In the digital era, many payments have switched to using digital payments. One of them that is often used by the public is the ShopeePay digital wallet. Shopeepay continues to expand its wings to attract consumers, through promotional media and ease of transactions. This aims to make it easier for consumers to carry out transactions. This research aims to analyze the influence of cashback promotions and ease of transactions simultaneously and partially on the decision to use the Shopeepay digital wallet as a digital payment. This study used a quantitative method and data management using multiple linear regression analysis. Statistical testing in this study used the t test, F test, and R Square. Sampling was carried out in this study using a purposive sampling technique. The research results show that cashback promotions and ease of transactions simultaneously have a significant influence on the decision to use the Shopeepay digital wallet. The results of this research also partially show that the cashback promotion variable has a significant influence on the decision to use the Shopeepay digital wallet, that is, the t value is 4.467 > t table 2.006 with a significant value of 0.000. Meanwhile, the transaction ease variable partially has a significant effect on the decision to use the Shopeepay digital wallet, that is, the T value is 4.241 > T table 2.006 with a significant value of 0.000. The results of the coefficient of determination test show that the decision to use can be explained by cashback promotions and ease of transactions amounting to 66.1%, while the remaining 33.9% is influenced by other variables not included in this research.